Role of moist and dry air advection in the development of Mediterranean tropical‐like cyclones (medicanes). (23rd December 2020) - Miglietta, Mario Marcello; Carnevale, Daniele; Levizzani, Vincenzo; Rotunno, Richard
Abstract: Two tropical‐like cyclones in the Mediterranean Sea, aka medicanes, are analysed herein by means of numerical simulations. The cyclones, which were recently investigated in Miglietta and Rotunno, Quarterly Journal of the Royal Meteorological Society, 2019, 145, are reconsidered in the present study, in which we focus on their respective preconditioning phases. In particular, here we analyse how local evaporation and/or long‐range transport of air masses may precondition the environment where the Mediterranean cyclones form. Numerical simulations indicate a rather different behaviour for the two cyclones. The first medicane (December 13–15, 2005) developed over the southern Mediterranean Sea, in a region of high low‐level humidity content, which existed before the cyclone formation; the air, originally dry over the eastern Balkans and the African mainland, gained humidity during its transit over the sea surface. In contrast, the second medicane (October 6–10, 1996) strongly intensified while benefitting from the intense sea‐surface fluxes due to the outbreak of Tramontane and Cierzo winds near the Balearic Islands, where the cyclone developed. Although limited to just two case studies, these results identify two different mechanisms conducive to an environment favourable for the intensification of medicanes in the western or southern Mediterranean. In addition, the role of dry air near the cyclone core, associated with upper‐tropospheric dry intrusions, is analysed. Sensitivity experiments were performed, constraining the relative humidity in the initial and boundary conditions to values above 50%. The advantage of this strategy is the ability to change the humidity content in the dry regions without modifying the associated strong potential vorticity anomalies. For both cases, we find that the humidity increase had the effect of inducing an earlier onset of cyclone development and of producing stronger, longer‐lasting vortices. Abstract : The intrusion of environmental air with lower moist entropy into the inner‐core convection is an important mechanism that affects the intensity of medicanes. The upper‐level intrusion of dry/cool air, transported from the lower stratosphere/upper troposphere, wraps around the embryonic warm column, mixes with warm/moist air and decreases θ e near the core of the cyclone (panel a), producing a loss in latent heat that results in a weaker intensification of the cyclone (panel c). If the intrusions of dry air in the initial phase were less intense (as in the sensitivity experiment RH50; panel b), the embryonic warm core could form and intensify earlier in a more favourable environment (panel d).